2017
DOI: 10.3233/jad-170383
|View full text |Cite
|
Sign up to set email alerts
|

Urine AD7c-NTP Predicts Amyloid Deposition and Symptom of Agitation in Patients with Alzheimer’s Disease and Mild Cognitive Impairment

Abstract: Background:Expression of neuronal thread protein (NTP), which is considered to be related to neuritic sprouting and neuronal death, may be elevated in brain tissue, cerebrospinal fluid, and even urine in patients with Alzheimer’s disease (AD).Objective:In this study, we analyzed the correlation between urine AD-associated NTP (AD7c-NTP) level, and amyloid-β (Aβ) deposition, and clinical symptoms in AD and mild cognitive impairment (MCI).Methods:Twenty-two patients with mild to moderate AD and 8 subjects with M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…For instance, Donovan et al found that higher amyloid‐beta burden (position emission tomography measures of cortical aggregate amyloid beta) was related to increased anxious‐depressive symptoms, even in cognitively healthy older people . Another study showed that amyloid deposition strongly correlated with agitation in patients with AD and MCI . Experimental studies with AD demonstrated that physical exercise can decrease significantly amyloid‐β 42 protein in animal brains .…”
Section: Potential Mechanisms Of Physical Activity On Npsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Donovan et al found that higher amyloid‐beta burden (position emission tomography measures of cortical aggregate amyloid beta) was related to increased anxious‐depressive symptoms, even in cognitively healthy older people . Another study showed that amyloid deposition strongly correlated with agitation in patients with AD and MCI . Experimental studies with AD demonstrated that physical exercise can decrease significantly amyloid‐β 42 protein in animal brains .…”
Section: Potential Mechanisms Of Physical Activity On Npsmentioning
confidence: 99%
“…78 Another study showed that amyloid deposition strongly correlated with agitation in patients with AD and MCI. 79 Experimental studies with AD demonstrated that physical exercise can decrease significantly amyloid-β 42 protein in animal brains. 80,81 Similarly, human studies indicated that low exercisers had higher mean levels of brain amyloid than high exercisers in autosomal dominant AD mutation carriers and that high-intensity aerobic exercise decreases plasma concentrations of Aβ 42 in patients with MCI.…”
Section: Cognitive Enhancer Effectsmentioning
confidence: 99%
“…In addition, AD7c-NTP is positively associated with phosphorylated tau accumulation in central neurons and cerebrospinal fluid (CSF) in AD patients 31 , 32 . Urinary AD7c-NTP level has been shown to have high sensitivity and specificity in predicting amyloid-β deposition in AD and mild cognitive impairment (MCI) 33 . Moreover, some studies found increased AD7c-NTP concentration in cerebrospinal fluid and urine in the early course of neurodegeneration in AD, which is positively associated with AD severity 34 - 37 .…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9] The urinary AD7c-NTP has been shown to have a high sensitivity and specificity for the diagnosis in AD and MCI. 9,[16][17][18] Several studies have suggested that urinary AD7c-NTP is a useful biomarker and may be widely used to screen the risk of elderly individuals with MCI and AD. [15][16][17][18][19][20] However, to the best of our knowledge, no previous urinary AD7c-NTP level studies tried to distinguish patients with aMCI from patients with naMCI using urinary AD7c-NTP as a biomarker.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, most previous studies regarding the urinary AD7c-NTP levels of the patients with MCI were performed with relatively brief neuropsychological tests that are not cognitive domain-specific. [5][6][7][8][9] More comprehensive cognitive domain-specific standardized neuropsychological tests are required to separate patients with MCI into amnestic and nonamnestic groups. Our study was performed through a neuropsychological screening battery of different cognitive domains to divide patients with MCI into amnestic and nonamnestic groups.…”
Section: Discussionmentioning
confidence: 99%